2006
DOI: 10.1002/masy.200650509
|View full text |Cite
|
Sign up to set email alerts
|

On the Escape Transition of a Tethered Gaussian Chain; Exact Results in Two Conjugate Ensembles

Abstract: Summary: Upon compression between two pistons an end‐tethered polymer chain undergoes an abrupt transition from a confined coil state to an inhomogeneous flower‐like conformation that is partially escaped from the gap. In the thermodynamic limit the system demonstrates a first‐order phase transition. A rigorous analytical theory of this phenomenon for a Gaussian chain is presented in two ensembles: a) the H‐ensemble, in which the distance H between pistons plays the role of the control parameter, and b) the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…At the transition point, the average order parameter S =< s > jumps from s imp eq to s esc eq . The Landau function allows one to analyze metastable states and to define the two lines where either one of the metastable minima vanishes [16]. Theoretical predictions for the escape transition of a Gaussian chain are summarized in Table I and…”
Section: Escape For a 2d Gaussian Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…At the transition point, the average order parameter S =< s > jumps from s imp eq to s esc eq . The Landau function allows one to analyze metastable states and to define the two lines where either one of the metastable minima vanishes [16]. Theoretical predictions for the escape transition of a Gaussian chain are summarized in Table I and…”
Section: Escape For a 2d Gaussian Chainmentioning
confidence: 99%
“…A phenomenon that was called escape transition occurs upon progressive squeezing an end-grafted polymer chain between two pistons and has attracted great interest [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. At weak deformation the chain is compressed uniformly into a relatively thick pan-cake conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of a polymer system with non-conventional phase transition is an end-grafted chain compressed between two pistons and undergoing the so-called escape transition. 24,37…”
Section: Abnormal Microcanonical Thermodynamicsmentioning
confidence: 99%
“…In the isometric ensemble the position of the chain ends is employed as a control parameter, fixing also the end-to-end distance, while in the isotensional case the control parameter is represented by the force applied on one loose end. The conditions under which the equivalence between these two ensembles can be obtained have been investigated in many works, both from a theoretical point of view [21,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and by means of computer simulations [41,42,43,44,45,46,47,48,49,50]. Some of the authors concluded that ensembles are equivalent in the infinitely long chain limit for a Gaussian chain, [30,47] as well as for a generic chain [21] and toy lattice chain models [21,35,36].…”
Section: Introductionmentioning
confidence: 99%